Prevalence and clinical predictors for early post-operative urinary retention in patients undergoing pelvic reconstructive surgeries: a prospective cohort study - Vijjeswarapu, Annie P.; Londhe, Vaibhav; Gowri, Mahasampath; Kekre, Aruna; Kekre, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pelvic organ prolapse (POP) has a significant impact on quality of life. Post-operative voiding dysfunction is seen in 2.5 to 24% of patients following pelvic reconstructive surgery. Risk factors like age of the patient, size of the genital hiatus and stage of prolapse are known to be associated with early post-operative voiding disorders. Methods: This is a prospective cohort study done in Christian Medical College, Vellore over one year. Patients with stage II to IV pelvic organ prolapse who underwent pelvic reconstructive surgery were observed post operatively for covert and overt urinary retention. Inability to void accompanied by pain and discomfort is defined as overt retention. Early post-operative urinary retention (POUR) is retention of urine in the first 72 hours postoperatively. Covert retention is defined as a non-painful bladder with chronic high post void residue. Chi- square test or Fisher’s exact test was used to assess the association between the clinical predictors and early post-operative urinary retention in univariate analysis. Results: In this study, 75 patients were recruited. Nine patients had POUR. Among the patients who had post-operative urinary retention, 77.78% had stage III pelvic organ prolapse (n=7). P value was 0.042. The prevalence of early POUR after pelvic reconstructive surgery was 12.85 % (n=9). A 55.55% had covert retention (n=5) and 44.44% patients had overt retention (n=4). Conclusions: The prevalence of early POUR after pelvic reconstructive surgery was 12.85%. Stage of the prolapse was an independent predictor for early postoperative urinary retention.